Monarchy as private property government. A chiefly methodological critique - Slenzok, Norbert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Hans-Hermann Hoppe famously argued that monarchy is superior to democracy insofar as property rights protection is concerned. The present paper calls this claim into question, with much of the heavy lifting being done by methodological ponderings. More specifically, it is demonstrated that instead of a priori, praxeological truths, Hoppe’s monarchy theory offers an ideal type of the politician bestowed with an inheritable title to the throne. Against this background, the ideal type in question is shown to be faulty in that it treats monarchs as capitalist landowners of sorts, thereby overlooking strictly political incentives they face, which can predictably push them in directions inimical to free markets.
Keywords: praxeology; sociology; Austrian methodology; time preference; ideal type; apriorism; Hans-Hermann Hoppe